Value of C-Reactive Protein in Predicting Left Ventricular Remodelling in Patients with a First ST-Segment Elevation Myocardial Infarction. (2nd September 2012) - Swiatkiewicz, Iwona; Kozinski, Marek; Magielski, Przemyslaw; Fabiszak, Tomasz; Sukiennik, Adam; Navarese, Eliano Pio; Odrowaz-Sypniewska, Grazyna; Kubica, Jacek
Abstract : Objective . To assess the value of C-reactive protein (CRP) in predicting postinfarct left ventricular remodelling (LVR). Methods. We measured in-hospital plasma CRP concentrations in patients with a first ST-segment elevation myocardial infarction (STEMI). Results . LVR was present at 6 months in 27.8% of 198 patients. CRP concentration rose during the first 24 h, mainly in LVR group. The prevalence of LVR was higher in patients from the highest quartile of CRP concentrations at 24 h as compared to those from any other quartile (odds ratio (OR) 3.48, 95% confidence interval (95% CI) 1.76–6.88). Multivariate analysis identified CRP concentration at 24 h (OR for a 10 mg/L increase 1.29, 95% CI 1.04–1.60), B-type natriuretic peptide at discharge (OR for a 100 pg/mL increase 1.21, 95% CI 1.05–1.39), body mass index (OR for a 1 kg/m 2 increase 1.10, 95% CI 1.01–1.21), and left ventricular end-diastolic volume (OR for a 1 mL increase 0.98, 95% CI 0.96-0.99) as independent predictors of LVR. The ROC analysis revealed a limited discriminative value of CRP (area under the curve 0.61; 95% CI 0.54–0.68) in terms of LVR prediction. Conclusions . Measurement of CRP concentration at 24 h after admission possesses a significant but modest value in predicting LVR after a first STEMI.